Comparison of Five Common Analyzers in the Measurement of Chemistry Analytes in an Authentic Cohort of Body Fluid Specimens. Issue 1 (31st January 2022) - Block, Darci R; Cotten, Steven W; Franke, Deanna; Mbughuni, Michael M
Abstract: Objectives: Interpretation of body fluid (BF) results is based on published studies and clinical guidelines. The aim of this study is to determine whether the assays from five common commercial vendors produce similar results in BFs for 12 analytes in a BF cohort. Methods: BFs (n = 25) and serum (n = 5) were analyzed on five instruments (Roche cobas c501, Ortho 5600, Beckman AU5800 and DXI800, Siemens Vista 1500, and Abbott Architect c8000) to measure albumin, amylase, total bilirubin, cholesterol, creatinine, glucose, lactate dehydrogenase (LDH), lipase, total protein, triglycerides, urea nitrogen, and carcinoembryonic antigen. Deming regression and Bland-Altman analysis were used for method comparison to Roche. Results: Results were significantly different from Roche for LDH and lipase on Ortho and lipase on Siemens but similar for both BFs and serum. BF differences were larger than serum differences when measuring creatinine, glucose, and urea nitrogen on Ortho and glucose on Siemens. Conclusions: Five instruments used to perform BF testing produce results that are not significantly different except for lipase and LDH measurements. Bias of similar magnitude observed in both BF and serum should not affect interpretation. Further investigations into Ortho and Siemens measuring glucose and Ortho measuring creatinine and urea nitrogen are warranted.